Biomimetic Dentin Remineralization Using Amino Acid-Modified Nanofibrous Scaffolds: A Review - Krishnan, Aruna; Raghu, Sandhya; Somasundaram, S Jayalakshmi (Journal of Neonatal Surgery, 2025)
Dentin demineralization, a hallmark of dental caries, poses a significant challenge to the long-term preservation of tooth structure and function. Traditional remineralization approaches often fail to restore the intrafibrillar mineral architecture necessary for mechanical resilience. In recent years, biomimetic strategies have emerged as promising alternatives, leveraging analogues of non-collagenous proteins (NCPs) and functional scaffolds to replicate natural dentinogenesis. Electrospun nanofibrous scaffolds, particularly those fabricated from polycaprolactone (PCL) and reinforced with nanohydroxyapatite (nHA), have demonstrated substantial potential in mimicking the extracellular matrix and promoting hierarchical mineral deposition. Moreover, acidic amino acids such as glutamic acid and its polymeric derivatives have shown remarkable efficacy in stabilizing amorphous calcium phosphate (ACP) and facilitating its transformation into hydroxyapatite within collagen matrices. This review synthesizes current knowledge on dentin ultrastructure, demineralization mechanisms, biomineralization pathways, and the design of scaffold-based delivery systems. It highlights emerging evidence supporting the integration of glutamic acid into PCL/nHA nanofibrous scaffolds for functional dentin regeneration. While these strategies mark a significant advancement in regenerative dentistry, clinical translation requires further investigation into long-term biocompatibility, ion release dynamics, and scaffold–cell interactions. This review underscores the potential of amino acid-based scaffolds in reshaping the future of biologically guided dentin remineralization.